Modeling camera coverage using imagery techniques for surveillance applications - Altahir, A.A. (Institute of Electrical and Electronics Engineers Inc., 2014)
Modeling the camera coverage is evidently indispensable to meet the requirements of a variety of visual sensor related applications. It is critical to be able to compute the camera coverage and to plan the related application accordingly. However, it is well known that camera coverage can be modeled geometrically. In contrast, tackling the camera visibility in arbitrary scenario is usually the challenging part of the model. This work illustrates the theoretical bases of camera modeling. In the same context, the paper introduces a camera coverage model based on a combination of imagery and computer graphic techniques. The imagery part of the model handles the computations of the camera coverage in an arbitrary digitized two dimensional map, while the camera visibility is traced based on computer graphics line drawing algorithm. The proposed model is capable of computing the camera coverage area in highly occluded scenes. Â© 2014 IEEE.